PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN KOMUNIKASI TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN SERENGAN KOTA SURAKARTA - Rahayu Triastity, Giyarni, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
Teacher performance in a school has been influenced by many factors. This study aims at analizing the significant influence of leadership style, motivation, and communication on teacher performance, and finding out the most dominant influence on teacher performance. The population is all of Sekolah Dasar (SD) teacher in Kecamatan Serengan Kota Surakarta with the number 250. The sample has been taken by proportional random sampling and 48% or 120 teachers are found to be sample. This study uses qualitative and quantitative methods and uses questionnaire, documentation, and literature study for data collection technique. The study uses validity and realibility test to determine precision and accuracy of the data. Validity test result by significant level of 0,05 indicates all independent variables r count > r table. Reliability test result indicates all independent variables > cronbachs alpha.The result shows that leadership style, motivation, and communication simultaneously have insignificant influence on teacher performance. Influence testing partially sh that leadership style has positive but insignificant influence on teacher performance, motivation has positive but insignificant influence on teacher performance, communication has positive but insignificant influence on teacher performance. This is showed by t test results that all independent variables have significance value > 0,05, while the F test shows result of 0,041 < 0,05. Based on the regression coefficients, communication has the greatest value of 0,253. this indicates that communication has the most dominant influence compared to the other variables in making a positive impact on teacher performance.Keywords: leadership style, motivation, communication, performance